Assessment of relapse of skeletal open bite treatment in adult patients treated with molar intrusion using temporary anchorage devices and orthognathic surgery - a systematic review - Jnaneshwar, Poornima; Devasagayam, Davis; Rajaram, Krishnaraj; Venkatesan, Keerthi; Sampath, Arvind; Thandapani, Anandhita; Haridas, Arvind (Brazilian Dental Science, 2022)
Objective: The purpose of this study is to systematically assess the available evidence for relapse of skeletal open bite treatment using temporary anchorage devices and orthognathic surgery. Materials and Methods: Five electronic databases such as MEDLINE, COCHRANE, SCIELO, GOOGLE SCHOLAR, EMBASE were systematically searched up to June 2020. Methodological quality studies were graded by means of the Effective Public Health Practice Project (EPHPP) Quality Assessment Tool. Results: In total, 1005 studies were identified for screening, and 6 studies were eligible. The quality assessment tool showed moderate quality for all the studies. The immediate post treatment correction of open bite was better in the surgical studies than in the studies treated with TADs. Conclusion: Stability of treatment results of anterior openbite was comparable in cases treated in both the treatment modalities. Relapse of anterior open bite was associated with cases in which the posttreatment overbite was minimal. Overbite seems to be more stable when only the maxilla has been operated on than with bi-maxillary surgeries. Counterclockwise rotation of the mandible with subsequent reduction of anterior facial height was better in surgical correction than through TADs. KEYWORDS Skeletal open bite; Temporary anchorage devices; LeFort 1 impaction; Bi-maxillary surgery.